WEBVTT
00:00:01.320 --> 00:00:06.870
In this video, weβll learn how to find the derivatives of the inverses of trigonometric functions.
00:00:07.300 --> 00:00:10.940
We will learn how to do this by using implicit differentiation.
00:00:11.190 --> 00:00:19.570
And thus, it is important that you understand how to apply the chain rule, if not have a thorough understanding of how implicit differentiation works, before watching this video.
00:00:20.270 --> 00:00:30.000
After deriving the derivatives of the inverse trigonometric functions, weβll consider the application of these derivatives to more complicated inverse trigonometric functions.
00:00:31.010 --> 00:00:38.750
Before we look at finding the derivative of our inverse trigonometric functions, letβs just quickly consider the function π¦ equal sin of π₯.
00:00:39.110 --> 00:00:40.960
Remember, π₯ is a real number.
00:00:41.510 --> 00:00:47.200
And of course, since weβre performing calculus with a trigonometric function, we need to make sure this is measured in radians.
00:00:47.840 --> 00:00:53.010
For this function, we can say that π₯ is equal to the inverse sin of π¦.
00:00:53.290 --> 00:00:56.340
This subscript negative one denotes the inverse function.
00:00:56.790 --> 00:01:03.810
Remember though without restricting the domain of arc sin of π₯ or inverse sin of π₯, the function is going to be many to one.
00:01:04.330 --> 00:01:09.020
We, therefore, restrict the domain for π of π₯ equals inverse sin of π₯.
00:01:09.180 --> 00:01:13.550
And we say that π₯ has to be greater than or equal to negative one and less than or equal to one.
00:01:14.130 --> 00:01:24.270
If we go back to the function π₯ equals the inverse sin of π¦, we can, therefore, see that π₯ will take values greater than or equal to negative π by two and less than or equal to π by two.
00:01:24.860 --> 00:01:26.750
Weβll also need to recall the chain rule.
00:01:27.450 --> 00:01:37.330
This says that if π¦ is some function in π’ and π’ is some differentiable function in π₯, then dπ¦ by dπ₯ is equal to dπ¦ by dπ’ times dπ’ by dπ₯.
00:01:37.760 --> 00:01:41.940
Weβll now use everything weβve seen here to find the derivative of the inverse sine function.
00:01:42.560 --> 00:01:46.620
Find the derivative of the inverse sine function with respect to π₯.
00:01:47.010 --> 00:01:51.050
Weβre differentiating the inverse sin of π₯ with respect to π₯.
00:01:51.260 --> 00:01:54.660
So weβre going to begin by letting π¦ be equal to the inverse sin of π₯.
00:01:54.920 --> 00:01:58.570
Then we can say that π₯ must be equal to sin of π¦.
00:01:59.050 --> 00:02:02.670
Weβre going to differentiate both sides of this equation with respect to π₯.
00:02:02.830 --> 00:02:07.030
So we say that d by dπ₯ of π₯ is equal to d by dπ₯ of sin of π¦.
00:02:07.490 --> 00:02:11.430
Well, the derivative of π₯ with respect to π₯ is quite straight forward; itβs one.
00:02:12.020 --> 00:02:19.260
But weβre going to need to use implicit differentiation which is a special case of the chain rule to differentiate sin π¦ with respect to π₯.
00:02:19.740 --> 00:02:24.170
The derivative of sin π¦ with respect to π¦ is cos π¦.
00:02:24.590 --> 00:02:34.270
So the derivative of sin π¦ with respect to π₯ is cos π¦ times the derivative of π¦ with respect to π₯ which is just dπ¦ by dπ₯.
00:02:34.470 --> 00:02:38.740
So we currently see that one is equal to cos of π¦ times dπ¦ by dπ₯.
00:02:39.140 --> 00:02:44.310
We divide both sides of this equation by cos π¦ to form an equation for the derivative.
00:02:44.760 --> 00:02:48.000
And we see that dπ¦ by dπ₯ is equal to one over cos π¦.
00:02:48.490 --> 00:02:49.620
Now, weβve got a bit of a problem.
00:02:49.620 --> 00:02:53.450
We do want an expression for the derivative in terms of π₯ not π¦.
00:02:54.000 --> 00:02:56.820
And remember, we said that π₯ was equal to sin of π¦.
00:02:57.210 --> 00:03:01.540
So weβll use the identity cos squared π plus sin squared π equals one.
00:03:01.570 --> 00:03:03.150
And Iβve replaced π with π¦.
00:03:03.690 --> 00:03:07.590
Weβll subtract sin squared π¦ from both sides of the equation.
00:03:07.900 --> 00:03:10.030
And then weβll take the square root of both sides.
00:03:10.030 --> 00:03:15.590
And we see that cos of π¦ is equal to the positive and negative square root of one minus sin squared π¦.
00:03:16.060 --> 00:03:21.660
Remember, inverse sin is restricted to the closed interval negative π by two to π by two.
00:03:22.010 --> 00:03:34.130
By our definition, that means π¦ must be greater than or equal to [negative] π by two and less than or equal to π by two which, in turn, means cos of π¦ must be greater than or equal to zero and less than or equal to one.
00:03:34.990 --> 00:03:40.940
And thatβs because in the interval π¦ is greater than or equal to negative π by two and less than or equal to π by two.
00:03:41.290 --> 00:03:43.920
The smallest value cos of π¦ weβll take is zero.
00:03:43.920 --> 00:03:45.220
And the greatest value is one.
00:03:45.780 --> 00:03:51.200
And what this means here is weβre going to take the positive square root of one minus sin squared π¦ only.
00:03:51.660 --> 00:03:54.290
We can now replace sin of π¦ with π₯.
00:03:54.290 --> 00:03:57.810
And we see that cos of π¦ is equal to the square root of one minus π₯ squared.
00:03:58.500 --> 00:04:04.170
And, therefore, dπ¦ by dπ₯ equals one over the square root of one minus π₯ squared.
00:04:04.710 --> 00:04:07.370
And we found the derivative of the inverse sin of π₯.
00:04:07.370 --> 00:04:15.070
Itβs one over the square root of one minus π₯ squared for values of π₯ in the range π₯ is greater than negative one and less than one.
00:04:16.650 --> 00:04:22.420
In our next example, weβll consider an alternative method that will help us find the derivative of the inverse cosine function.
00:04:23.700 --> 00:04:27.020
This time, weβre going to need to know the inverse function theorem.
00:04:27.800 --> 00:04:40.810
This says that if π is a differentiable function with a continuous inverse π prime and π prime of π is not equal zero, then not only is π invertible but it has a differentiable inverse.
00:04:41.160 --> 00:04:52.150
Such that the derivative of the inverse of π at some π equals π of π is equal to one over the derivative of π at π.
00:04:52.800 --> 00:04:59.060
This is sometimes written simply as dπ₯ by dπ¦ is equal to one over dπ¦ by dπ₯.
00:04:59.380 --> 00:05:03.560
Letβs see how this might help us when differentiating the inverse cosine function.
00:05:04.780 --> 00:05:11.470
Find the derivative of the inverse cos of π₯ over π with respect to π₯, where π is not equal to zero.
00:05:12.330 --> 00:05:16.730
Weβll begin by letting π¦ be equal to the inverse cos of π₯ over π.
00:05:17.180 --> 00:05:21.770
This can be alternately written as π₯ over π equals cos of π¦.
00:05:22.160 --> 00:05:24.870
And we can then multiply both sides by π.
00:05:24.870 --> 00:05:27.940
And we see that π₯ is equal to π times cos of π¦.
00:05:28.380 --> 00:05:32.740
Weβre going to differentiate our expression for π₯ with respect to π¦.
00:05:33.160 --> 00:05:36.150
In other words, weβre going to find dπ₯ by dπ¦.
00:05:36.570 --> 00:05:42.090
Weβll use the general result that the derivative of cos of π₯ with respect to π₯ is negative sin of π₯.
00:05:42.310 --> 00:05:46.200
And we see that dπ₯ by dπ¦ must be equal to negative π sin of π¦.
00:05:46.780 --> 00:05:53.820
Now, before we perform the next step we need to recall the fact that for the inverse trigonometric functions, we restrict their domains.
00:05:54.170 --> 00:06:00.770
And we know that the domain of the inverse cos of π₯ or our cos of π₯ is greater than or equal to zero and less than or equal to π.
00:06:01.230 --> 00:06:04.970
This means that π¦ must be greater than or equal to zero and less than or equal to π.
00:06:05.350 --> 00:06:07.740
Now, weβre going to use the inverse function theorem.
00:06:08.020 --> 00:06:15.340
So weβre going to take values of π¦ greater than zero and less than π, such that sin of π¦ is not equal to zero.
00:06:15.790 --> 00:06:25.810
Using this criteria, we can use dπ₯ by dπ¦ equals one over dπ¦ by dπ₯ which can be rearranged to say that dπ¦ by dπ₯ equals one over dπ₯ by dπ¦.
00:06:26.280 --> 00:06:31.520
And we see that, for our case, dπ¦ by dπ₯ equals one over negative π sin of π¦.
00:06:32.320 --> 00:06:35.550
And we have an expression for the derivative in terms of π¦.
00:06:35.550 --> 00:06:37.510
Remember, we want this to be in terms of π₯.
00:06:37.830 --> 00:06:40.530
We said that π₯ over π equals cos of π¦.
00:06:40.940 --> 00:06:50.530
So weβll use the fact that sin squared π¦ plus cos squared π¦ equals one and rearrange this to say that sin π¦ equals plus or minus the square root of one minus cos squared π¦.
00:06:51.110 --> 00:06:55.160
When π¦ is between zero and π, sin π¦ is greater than zero.
00:06:55.410 --> 00:06:57.820
So in fact, weβre only interested in the positive root.
00:06:58.120 --> 00:07:01.320
So weβll replace this in our expression for the derivative.
00:07:01.320 --> 00:07:05.910
And we get negative one over π times the square root of one minus cos squared π¦.
00:07:06.330 --> 00:07:13.640
We then replace cos π¦ with π₯ over π and change π₯ over π all squared to π₯ squared over π squared.
00:07:13.950 --> 00:07:15.790
And then we bring π into the square root.
00:07:15.820 --> 00:07:21.090
And we see that dπ¦ by dπ₯ is equal to negative one over the square root of π squared minus π₯ squared.
00:07:21.390 --> 00:07:32.330
So d by dπ₯ of the inverse cos of π₯ over π is equal to negative one over the square root of π squared minus π₯ squared for values of π₯ between negative π and π.
00:07:33.280 --> 00:07:40.430
In our next example, weβll consider how we might apply the process thatβs used so far to find the derivative of the inverse tangent function.
00:07:42.110 --> 00:07:48.410
Find an expression for the derivative of π¦ equals the inverse tan of ππ₯ in terms of π₯.
00:07:48.860 --> 00:07:54.820
Since π¦ is equal to the inverse tan of ππ₯, we can write ππ₯ as being equal to tan π¦.
00:07:55.340 --> 00:08:00.610
Weβre going to use implicit differentiation to find the derivative of both sides of this equation.
00:08:01.070 --> 00:08:03.970
The derivative of ππ₯ with respect to π₯ is simply π.
00:08:04.550 --> 00:08:13.840
And the derivative of tan π¦ with respect to π₯ is equal to the derivative of tan π¦ with respect to π¦ times the derivative of π¦ with respect to π₯.
00:08:14.050 --> 00:08:16.500
The derivative of tan π₯ is sec squared π₯.
00:08:16.640 --> 00:08:19.790
And the derivative of π¦ with respect to π₯ is dπ¦ by dπ₯.
00:08:19.990 --> 00:08:23.870
So we see that π is equal to sec squared π¦ times dπ¦ by dπ₯.
00:08:24.100 --> 00:08:29.540
Dividing through by sec squared π¦ and we see that dπ¦ by dπ₯ equals π over sec squared π¦.
00:08:30.100 --> 00:08:33.890
Weβre going to need to represent our equation for the derivative in terms of π₯.
00:08:34.220 --> 00:08:36.580
So weβll use this trigonometric identity.
00:08:36.700 --> 00:08:39.520
One plus tan squared π₯ equals sec squared π₯.
00:08:39.840 --> 00:08:44.340
This means we can write dπ¦ by dπ₯ as π over one plus tan squared π¦.
00:08:44.880 --> 00:08:47.740
And then we replaced tan π¦ with ππ₯.
00:08:47.900 --> 00:08:55.850
And we see the expression for the derivative of π¦ equals the inverse tan of ππ₯ is π over one plus ππ₯ squared.
00:08:57.360 --> 00:09:02.460
Similar rules can be applied to help us find the derivative of the inverse cotangent function.
00:09:02.770 --> 00:09:10.150
We find that the derivative of the inverse of cotangent of π of π₯ is equal to negative π over one plus ππ₯ squared.
00:09:10.850 --> 00:09:14.390
The inverse cosecant and secant functions are a little more unusual.
00:09:14.590 --> 00:09:19.000
So weβll consider next how to find the derivative of the inverse cosecant function.
00:09:20.210 --> 00:09:23.900
Find d by dπ₯ of the inverse cosecant of π₯.
00:09:24.180 --> 00:09:28.220
We begin by letting π¦ be equal to the inverse cosecant of π₯.
00:09:28.400 --> 00:09:29.890
And this means we can rewrite this.
00:09:29.890 --> 00:09:32.670
And we can say that π₯ is equal to the cosecant of π¦.
00:09:32.990 --> 00:09:37.790
Weβre next going to use implicit differentiation to find the derivative of both sides of this equation.
00:09:38.290 --> 00:09:40.990
The derivative of π₯ with respect to π₯ is simply one.
00:09:41.660 --> 00:09:50.390
Then the derivative of cosec π¦ with respect to π₯ is equal to the derivative of cosec π¦ with respect to π¦ times dπ¦ by dπ₯.
00:09:50.630 --> 00:09:55.760
And the derivative of cosec π¦ with respect to π¦ is negative cosec π¦ cot π¦.
00:09:56.310 --> 00:10:00.880
So we see that one is equal to negative cosec π¦ cot π¦ times dπ¦ by dπ₯.
00:10:01.300 --> 00:10:09.700
Now, we know that, for the inverse cosecant function, π¦ must be greater than negative π by two and less than π by two and not equal to zero.
00:10:10.000 --> 00:10:14.430
Using these restrictions cosec π¦ cot π¦ cannot be equal to zero.
00:10:14.760 --> 00:10:18.470
So we can divide through by negative cosec π¦ cot π¦.
00:10:18.890 --> 00:10:21.170
And we see that dπ¦ by dπ₯ is as shown.
00:10:21.630 --> 00:10:25.510
We want to represent our equation for the derivative in terms of π₯.
00:10:25.810 --> 00:10:31.700
So weβll use this trigonometric identity cot squared π¦ plus one equals cosec squared π¦.
00:10:32.170 --> 00:10:39.260
And we can rewrite this to say that cot of π¦ is equal to the positive and negative square root of cosec squared π¦ minus one.
00:10:39.960 --> 00:10:43.620
We put this into the equation for the derivative in place of cot of π¦.
00:10:43.960 --> 00:10:46.750
And we then use the fact that π₯ is equal to cosec π¦.
00:10:47.270 --> 00:10:51.240
But we are going to need to make a decision on the sine of the derivative.
00:10:51.280 --> 00:10:55.000
And it can help here to look at the graph of the inverse cosecant function.
00:10:55.440 --> 00:11:02.940
Notice how, for all values of π₯ in the range of the function, the derivative of the slope of the tangent is negative.
00:11:03.510 --> 00:11:08.860
And we, therefore, use the absolute value to ensure that our derivative is always negative.
00:11:09.020 --> 00:11:16.550
We say that dπ¦ by dπ₯ is equal to the negative of the absolute value of one over π₯ times the square root of π₯ squared minus one.
00:11:16.970 --> 00:11:22.270
Since one and the square root of π₯ squared minus one are always positive, we can rewrite this as shown.
00:11:23.120 --> 00:11:35.080
So the derivative of the inverse cosecant function π₯ with respect to π₯ is negative one over the modulus or absolute value of π₯ times the square root of π₯ squared minus one.
00:11:36.790 --> 00:11:41.190
A similar process can be applied to help us find the derivative of the inverse secant function.
00:11:41.860 --> 00:11:46.570
And we have the derivatives of all of the inverse trigonometric functions we require.
00:11:47.950 --> 00:11:53.460
Itβs useful to commit these results to memory but also be prepared to derive them where necessary.
00:11:54.000 --> 00:11:56.580
Weβll now have a look at the application of these results.
00:11:57.380 --> 00:12:03.130
Evaluate the derivative of the inverse cotangent of one over π₯ with respect to π₯.
00:12:03.710 --> 00:12:07.610
Here, we have a function of a function or a composite function.
00:12:07.990 --> 00:12:11.360
Weβre, therefore, going to need to use the chain rule to find the derivative.
00:12:11.740 --> 00:12:22.040
This says that if π and π are differentiable functions such that π¦ is π of π’ and π’ is π of π₯, then dπ¦ by dπ₯ is equal to dπ¦ by dπ’ times dπ’ by dπ₯.
00:12:22.330 --> 00:12:24.790
Weβll let π’ be equal to one over π₯.
00:12:24.900 --> 00:12:27.600
Then π¦ is equal to the inverse cot of π’.
00:12:28.180 --> 00:12:31.910
To apply the chain rule, we need to find the derivative of both of these functions.
00:12:32.010 --> 00:12:35.390
And with π’ it can be useful to write it as π₯ to the negative one.
00:12:35.790 --> 00:12:41.270
Then dπ’ by dπ₯ is negative π₯ to negative two or negative one over π₯ squared.
00:12:41.610 --> 00:12:45.390
We can then use the general derivative of the inverse cotangent function.
00:12:45.810 --> 00:12:52.850
And we see that dπ¦ by dπ’ is equal to negative one over one plus π’ squared. dπ¦ by dπ₯ is the product of these.
00:12:52.950 --> 00:12:57.170
Itβs negative one over π₯ squared times negative one over one plus π’ squared.
00:12:57.370 --> 00:13:01.030
We can replace π’ with one over π₯ and then multiply through.
00:13:01.520 --> 00:13:08.320
And we see that the derivative of the inverse cotangent of one over π₯ with respect to π₯ is one over π₯ squared plus one.
00:13:10.480 --> 00:13:17.430
Did you notice that the derivative of the inverse cotangent of one over π₯ is equal to the derivative of the tangent of π₯?
00:13:17.710 --> 00:13:19.960
This is, in fact, no accident.
00:13:20.710 --> 00:13:26.910
And we can use the identity the inverse cotangent of one over π₯ equals the inverse tan of π₯.
00:13:27.140 --> 00:13:30.860
That could have saved us a little bit more time in this previous example.
00:13:31.800 --> 00:13:37.960
Evaluate the derivative of the inverse sin of the square root of one minus π₯ squared with respect to π₯.
00:13:38.320 --> 00:13:41.410
Here, we have a function of a function or a composite function.
00:13:41.870 --> 00:13:44.380
So weβll use the chain rule to find its derivative.
00:13:44.620 --> 00:13:52.760
This says that if π¦ is some function in π’ and π’ is some function in π₯, then dπ¦ by dπ₯ is equal to dπ¦ by dπ’ times dπ’ by dπ₯.
00:13:53.100 --> 00:13:56.260
Weβll let π’ be equal to the square root of one minus π₯ squared.
00:13:56.490 --> 00:14:01.080
Which can, of course, alternatively be written as one minus π₯ squared to the power of one-half.
00:14:01.460 --> 00:14:03.760
Then π¦ is equal to the inverse sin of π’.
00:14:04.230 --> 00:14:08.480
To apply the chain rule, weβre going to need to find the derivative of both of these functions.
00:14:08.760 --> 00:14:15.950
The derivative of the inverse sin of π’ with respect to π’ is one over the square root of one minus π’ squared.
00:14:16.370 --> 00:14:21.950
And we can use the general power rule to find the derivative of one minus π₯ squared to the power of one-half.
00:14:22.230 --> 00:14:30.270
Itβs a half times one minus π₯ squared to the negative one-half times the derivative of the bit inside the brackets which is negative two π₯.
00:14:30.520 --> 00:14:35.330
That can be written as negative π₯ times one minus π₯ squared to the power of negative one-half.
00:14:35.650 --> 00:14:43.370
dπ¦ by dπ₯ is, therefore, negative π₯ over the square root of one minus π₯ squared times one over the square root of one minus π’ squared.
00:14:43.690 --> 00:14:47.250
We can replace π’ with one minus π₯ squared to the power of one-half.
00:14:47.430 --> 00:14:52.290
And the second fraction becomes one over the square root of one minus one minus π₯ squared.
00:14:52.640 --> 00:14:55.250
This further simplifies to one over π₯.
00:14:55.550 --> 00:14:57.090
And we divide through by π₯.
00:14:57.590 --> 00:15:02.890
And we see that the derivative of our function is negative one over the square root of one minus π₯ squared.
00:15:04.850 --> 00:15:07.750
Once again, weβve stumbled across an interesting result.
00:15:07.890 --> 00:15:15.640
That is that the derivative of the inverse sin of the square root of one minus π₯ squared is equal to the derivative of the inverse cos of π₯.
00:15:16.570 --> 00:15:25.050
This comes from the identity of the inverse sin of the square root of one minus π₯ squared is equal to the inverse cos of π₯, the values of π₯ between zero and one.
00:15:26.010 --> 00:15:31.310
Being familiar with this result could have reduced the amount of what we needed to do in this example.
00:15:32.450 --> 00:15:41.640
In this video, weβve seen that we can use implicit differentiation or the inverse function theorem to derive the formulae for the derivatives of inverse trigonometric functions.
00:15:42.170 --> 00:15:46.600
We saw that the derivatives of the inverse trigonometric functions are as shown.
00:15:47.160 --> 00:15:55.370
And we also saw that being familiar with certain trigonometric identities can sometimes significantly reduce the process of finding these derivatives.